BUS ACCIDENTS PREVENTION WITH AN INTEGRATED STEERING SYSTEM - Kher, V.K.; Tan , Chee Fai; Sarban Singh, Ranjit Singh (2012)
This paper is focused on improving the drivability of busses for preventing accidents. Bus accidents are not as frequent as car accidents but each bus accidents puts at least forty human lives in risk which is equivalent to eight saloon cars with the maximum allowable passengers. While there are many parts of the busses which can be looked into for improving the safety this paper is focusing on the steering systems. Nowadays, many automobile manufacturers have integrated safety systems into the steering systems for saloon cars and the results shown are positive. They are proven to be effective as the manufacturers have successfully commercialised their technologies. Similarly, a framework will be developed to implement steering system integrated with safety systems for busses. The suggested framework will be focused on overcoming a specific emergency scenario which bus drivers will encounter most commonly.